PENGGUNAAN TEKNIK TIME TOKEN ARENDS UNTUK MENUMBUHKAN SIKAP DEMOKRATIS PESERTA DIDIK DALAM PEMBELAJARAN SEJARAH (Penelitian Tindakan Kelas XI MIA 5 SMAN 1 Katapang) - Sumpena Kurniawan; Nana Supriatna; Yeni Kurniawati (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2017)
This research is motivated by the problems occured in learning history. The problems associated with student activity especially in democratic attitude. Their democratic attitude in the learning activity is considering low Departing from these problems, the researcher tried to apply the technique of “time token” to foster students democratic attitudes in the teaching of history. The reeseach method that used in this paper is Classroom Action Research with the approachment research design by Kemmis Mc. Taggart which conducted into several stages including planning, implementation, observation and reflection. Based on the observation, the democratic attitudes in class XI MIA 5 has increased, which is based on the number of cycles that have been made. Research provides students 97% increase in learning. In the end of the history learning using the time token technique can be resulting in the increase of students democratic attitudes.